Emerging Mapping Techniques for Autonomous Underwater Vehicles (AUVs) - Vanessa Lucieer; Alexander Forrest (2016)
Seafloor environments at ever increasing depths on the continental shelf are being resolved at ever higher resolutions as a result of changing sensor technologies and, in part, with the emergence of Autonomous Underwater Vehicles (AUVs) as stable survey platforms. The new age of underwater robots to act as platforms which we can use to deploy sensors to gather information in the ocean is only limited by our imagination. This chapter provides an overview of this technology for applications on the continental shelf. It explores the basic fundamentals of AUV operation and the types of associated instrumentation, the current state of commercial and academic activity and the broad disciplines across which AUVs are currently been employed. AUVs are highly effective tools for sampling in continental shelf marine environments because: (1) they are untethered and can conduct non-destructive sampling in remote habitats (e.g. under ice shelves and over complex terrain) and in depths > 1000 m; (2) they can repeat spatial surveys with a high degree of precision over time; and (3) they can be equipped with a wide range of tools and sensors to sample both physical, chemical and biological data. Unfortunately by the time this chapter is in print, it realistically will already be out of date, as a result of the speed of the technological advancement in this discipline of underwater engineering.